Political Economic Dilemmas of SAARC Member Countries in South Asia - Putra, Gilang Rizki Aji; Yunus, Nur Rohim; Abdurofiq, Atep (BULETIN ADALAH, 2023)
This article reviews the political economic dilemma faced by member countries of the South Asian Association for Regional Cooperation (SAARC) in South Asia. SAARC, as a regional cooperation forum, faces various challenges in promoting balanced and inclusive economic integration in the region. SAARC member countries show varying levels of economic development, while infrastructure inequality and dependence on certain economic sectors are major obstacles. This article highlights efforts to increase cooperation in trade, infrastructure investment, and policy harmonization as crucial steps to address these challenges. In the complex geopolitical context of South Asia, regional policy implementation is often faced with internal political constraints and coordination among SAARC member states. The conclusion of this article emphasizes the need for close cooperation and strong commitment from all parties involved to achieve inclusive and sustainable economic growth in the SAARC region.